Spectro‐Electrochemical Microfluidic Platform for Monitoring Multi‐Step Cascade Reactions. Issue 1 (1st August 2018) - Andersen, Nalin I.; Artyushkova, Kateryna; Matanović, Ivana; Hickey, David P.; Minteer, Shelley D.; Atanassov, Plamen
Abstract: Benefits of utilizing cascade reactions for chemical synthesis include minimizing waste and decreasing experimentation times. However, these complex systems lack an efficient screening platform for evaluating their progression. A paper‐based microfluidic platform was developed to monitor cascade systems without the need for off‐line product verification. Two types of paper‐based platforms were fabricated to facilitate this study: electrochemical and spectro‐electrochemical. Electrochemical platforms were integrated with stencil‐printed electrodes and used to perform electrochemical alcohol oxidation reactions with two derivatives of the organocatalyst TEMPO (TEMPO=2, 2, 6, 6‐tetramethylpiperidinyl‐N‐oxyl). The catalyst 4‐amino‐TEMPO (TEMPO‐NH2 ) was used as a model catalyst that was studied not immobilized and immobilized (pyrene‐amido‐TEMPO) on electrochemical platforms. These platforms were designed to provide quasi‐stationary flow allowing constant electrochemical data collection as catalytic reactions proceeded. TEMPO‐NH2 and pyrene‐amido‐TEMPO were evaluated for the partial oxidation of glycerol and its intermediates. In comparison to TEMPO‐NH2, the pyrene‐amido‐TEMPO catalyst produced higher current outputs. Spectro‐electrochemical platforms were integrated with stencil‐printed electrodes, and a surface enhanced Raman spectroscopy (SERS) detection zone. The spectro‐electrochemical platforms allowed for catalytic conversions at the electrodes and subsequent delivery of catalytically transformed analytes to a SERS detection zone for product analysis. This platform was demonstrated for pyrene‐amido‐TEMPO and was shown to convert glycerol to mesoxalic acid. The experimental procedures for making components of the spectro‐electrochemical device were described and include: preparation of the paper‐based platform, construction of stencil‐printed electrodes, and fabrication of SERS detection zones. These platforms provide an approach to analyzing multi‐step cascade chemical reactions. Abstract : Go with the flow : Paper‐based microfluidic platforms are fabricated to study catalytic cascade reactions found in the oxidation of glycerol. Electrocatalysts are compared and products from the reactions are verified with surface‐enhanced Raman spectroscopy (SERS).